Tracing the Emergence and Growth of Ecocritical Language - Bashir , Tabeeda Binti (South Asian Journal of Social Sciences and Humanities, 2020)
During the last few decades, the disturbance in the environmental conditions has given rise to a great threat to Earth and the organisms residing in it. Under these circumstances, a new theory of reading texts came into existence known as Ecocriticism. Ecocritism is a literary theory which shows the interconnectedness between the human and the non-human agency, but it has not yet achieved that attention which other theories have. In this context, ecocritics strive to influence readers and writers by introducing and developing a specific vocabulary in their works. This paper can assist readers in understanding how ecocritics have developed a vocab ulary of their own. This paper aims to find and trace the emergence of ecological linguistics and its growth. Also, the aim is to perform an up-to-date assessment of its current state. Since Ecolinguistics work upon the role language plays in the life-sustaining interactions of humans and their physical environment, the main aim is to explore this language as used by ecocritics in order to reach the eco-critical judgements about certain texts—both the provisional and the temporal judgements. The language has a soft, respectful and rigorous influence on the envi ronment, so in this perspective, ecocritics establish tools in order to determine the influence of narrative techniques and the structures on readers. Readers and writers encounter varied narra tive styles when discussing environment and ecology, this paper will show how the attempt to create a specific vocabulary in this regard will better solidify the foundations of this field